Assessment of uptake of cervical cancer screening services among women of reproductive age in Khwisero sub-county, Kakamega County, Kenya - Kiboche, James G.; Ogutu, Philip A.; Mustami, Anne Naliaka (International Journal Of Community Medicine And Public Health, 2020)
Background: Cervical cancer stands to be amongst the major contributors to cancer demises and morbidity in the world. It is also ranked fourth among the most frequent types of cancer among women. The objective was assessing uptake of services for cervical cancer screening amongst women in the reproductive age in Khwisero Sub County, Kakamega County, Kenya. Methods: Cross sectional descriptive study of 393 females from the age of eighteen to forty nine who were purposively sampled from was conducted. A questionnaire was administered by the interviewer. The data was collected, cleaned and entered in the analysis software (SPSS version 17). The Pearson Chi-square was used to conduct bivariate analysis in order to define the relationships between the variables having a level of significance at p<0.05. The presentation of the captured results was then done in pie-charts, graphs, charts and tables. Results: Of the 393 interviewed 16.8% had a cervical cancer screening done either through pap smear, VIA and VILI within the past year. Significant influencers of screening uptake were marriage, age, parity, and health providers’ support. Conclusions: There was a low level of awareness and knowledge on cervical cancer which resulted in low uptake levels of screening services which also influenced by other factors like age and marital status.